Academic vocabulary for L2 argumentative writing: Perspectives from Chinese university EFL learners - Changyong Min; Apisak Sukying (Studies in English Language and Education)
Academic vocabulary plays a critical role in L2 argumentative writing. Recent studies have specifically examined the importance of academic vocabulary and academic word lists for EAP and ESP learning and research. However, it is unclear how English as a Foreign Language (EFL) learners perceive academic vocabulary and the challenges they face using this vocabulary in university argumentative essays. The present study adopted a case study approach to investigate Chinese university EFL learners’ perceptions of, and problems with, academic vocabulary in an argumentative writing task. Five fourth-year advanced EFL learners were assigned to write an IELTS essay before participating in a one-on-one interview. The results indicated that while participants had a heightened awareness of the importance of academic vocabulary, they lacked a comprehensive understanding of this construct. More specifically, they knew little about the academic register, and their academic vocabulary size was small. Consequently, various problems arose in relation to the use of academic words in their argumentative writing, including word choice and the over-reliance on Chinese word meaning and word spelling knowledge. The EFL learners also reported that the biggest challenge to their academic writing was the lack of academic collocation knowledge. These findings have pedagogical implications for understanding the academic lexical problems facing Chinese EFL learners in their academic writing.